THE PHRASEOLOGICAL SYSTEM OF THE SWEDISH LANGUAGE AND PRINCIPLES OF ITS CLASSIFICATION - Temirova Farangis Anvarovna (Bright Mind Publishing, 2026)
This article examines the phraseological system of the Swedish language, focusing on the principles of its classification and structural organization. Swedish phraseology reflects both historical linguistic development and contemporary usage, encompassing idiomatic expressions, fixed collocations, and proverb-like units. The study identifies the main categories of Swedish phraseological units and analyzes the criteria used for their classification, including semantic, structural, and functional approaches. The findings highlight the importance of understanding the systematic nature of phraseology for linguistic research, language teaching, and contrastive studies. Additionally, the article emphasizes how phraseological structures contribute to the expressive and stylistic potential of the Swedish language.
Keywords: Swedish language, phraseology, idiomatic expressions, classification, semantic analysis, structural approach, functional approach.